Design Laboratory for Developing Students Competencies: Physical Education for Elementary School - Raharjo, Hermawan Pamot; Purakom, Atchara; Rahayu, Tandiyo; Kurniawan, Wahyu Ragil; Wijayanti, Dwi Gansar Santi (Jurnal Kesehatan Masyarakat, 2024)
Attention to student competence as prospective physical education teachers is very important. Physical education is not only learning about how to maintain health but also how to provide space for students to learn movement skills. Analysis in 2023 shows no laboratory that facilitates a special space for microteaching practice for prospective physical education teacher students at the elementary school level. This research aims to develop a basic physical education movement learning laboratory design for elementary school physical education study program students in 2023. The method used in this research is the research and development method. This type of development research is carried out to produce certain products and test the effectiveness of these products. The results of this research found that the suitability, safety, and usability of the products developed for users received a good response. Five questions addressed to lecturers and students as potential design users showed that on the first question, respondents gave a good response with an average of 72% regarding the placement and use of spatial layout. Next, regarding basic movement coverage, the result was 68.3%. Questions related to the suitability of material outcomes obtained a result of 65.1%. The percentage regarding aspects of ease and safety in use obtained a value of 55%, and regarding the usability and usefulness of the product, a response of 56.5% was obtained. This response concludes that the development product received a good response and support from the lecturers and students of the elementary school physical education study program. Suggestions for further research are the development of a laboratory with the concept of game activities by including elements of tactics and strategy.